Advancing Energy Development with MBene: Chemical Mechanism, AI, and Applications in Energy Storage and Harvesting - Kumar, Jai; Solangi, Nadeem Hussain; Neiber, Rana R.; Bai, Fangyuan; Charles, Victor; Zhai, Pengfei; Wang, Zhuanpei; Yang, Xiaowei (Nano-Micro Letters, 2026)
MXene derivatives are notable two-dimensional nanomaterials with numerous prospective applications in the domains of energy development. MXene derivative, MBene, diversifies its focus on energy storage and harvesting due to its exceptional electrical conductivity, structural flexibility, and mechanical properties. This comprehensive review describes the sandwich-like structure of the synthesized MBene, derived from its multilayered parent material and its distinct chemical framework to date. The fields of focus encompass the investigation of novel MBenes, the study of phase-changing mechanisms, and the examination of hex-MBenes, ortho-MBenes, tetra-MBenes, tri-MBenes, and MXenes with identical transition metal components. A critical analysis is also provided on the electrochemical mechanism and performance of MBene in energy storage (Li/Na/Mg/Ca/Li–S batteries and supercapacitors), as well as conversion and harvesting (CO2 reduction, and nitrogen reduction reactions). The persistent difficulties associated with conducting experimental synthesis and establishing artificial intelligence-based forecasts are extensively deliberated alongside the potential and forthcoming prospects of MBenes. This review provides a single platform for an overview of the MBene’s potential in energy storage and harvesting. Highlights: 1 Revealing the synergistic potential of MBene as an advanced material. 2 Comprehensive study into MBene chemistry and electrochemical efficacy. 3 The potential research for batteries, supercapacitors, CO2 reduction, and nitrogen reduction reactions is unveiled. 4 AI-driven predictions and limitations in experimental synthesis are addressed comprehensively.